2019
DOI: 10.1161/circinterventions.118.006928
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Variation in 90-Day Episode Payments After Percutaneous Coronary Intervention

Abstract: Background: Percutaneous coronary intervention (PCI) is a common and expensive procedure that has become a target for bundled payment initiatives. We described the magnitude and determinants of variation in 90-day PCI episode payments across a diverse array of patients and hospitals. Methods and Results: We linked clinical registry data from PCIs performed at 33 Michigan hospitals to 90-day episodes of care constructed using Medicare fee-for-service and commercial insurance claims from 1/2012-10/2016. Paymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The average age of the patients was 65.6 years. Obesity (body mass index > 30 kg/m 2 , 46.6%), diabetes mellitus (40.4%), dyslipidemia (84.5%), and hypertension (83.8%) chronic renal (26.4%) and chronic lung (17.6%) disease were the commonest comorbidities. The average pre-PCI left ventricular ejection fraction was 52.1%, and a large proportion (varying between 21%-47%) patients had a significant history of heart failure, coronary artery disease, myocardial infarction, peripheral artery disease, or previous cardiac interventions (PCI and/or coronary artery bypass graft(CABG)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of the patients was 65.6 years. Obesity (body mass index > 30 kg/m 2 , 46.6%), diabetes mellitus (40.4%), dyslipidemia (84.5%), and hypertension (83.8%) chronic renal (26.4%) and chronic lung (17.6%) disease were the commonest comorbidities. The average pre-PCI left ventricular ejection fraction was 52.1%, and a large proportion (varying between 21%-47%) patients had a significant history of heart failure, coronary artery disease, myocardial infarction, peripheral artery disease, or previous cardiac interventions (PCI and/or coronary artery bypass graft(CABG)).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, alternative payment models such as the Centers for Medicare and Medicaid Services (CMS) episode payment models (EPMs), commonly known as “bundled payments”, are accelerating hospitals to prepare for the shift in reimbursement from ‘payment for volume’ to ‘payment for value’. (2)…”
Section: Introductionmentioning
confidence: 99%
“…As health care costs continue to escalate with increasing prevalence of cardiovascular disease and constant advancement of medical technologies and equipment, the economic evaluations of health care delivery are essential. Previous studies have shown that a significant portion of post-PCI costs are related to hospital readmissions, lengths of stay, and post-procedural complications or post-acute care [ 20 22 ]. Using large readmission and administrative claim databases, analyzing hundreds of thousands of patients undergoing PCI, these studies have shown clear associations between longer lengths of stay and post-procedural complication rates with increased costs.…”
Section: Discussionmentioning
confidence: 99%
“…However, Medicare is introducing episode‐based reimbursement models and pioneering them on patients undergoing PCI. In one study, readmission was the major cause of variation in cost of the PCI episode 4 . Furthermore, Medicare is refining their methodology to identify differences in cost among individual operators 5 .…”
Section: Condition 30‐day Readmission Rate Cost Per Readmission Citationmentioning
confidence: 99%